Pengaruh Kualitas Sumber Daya Manusia dan Disipilin Kerja Terhadap Target Penerimaan Pajak Daerah Melalui Pelayanan Prima Pada Samsat Unit Pelaksana Teknis Wilayah Kabupaten Pinrang - Karmawati Karmawati (STIM-LPI Makassar, 2022)
The purpose of this study was to examine and analyze the effect of the quality of human resources and work discipline, both directly and indirectly on the target of local tax revenues through excellent service at the Samsat Technical Implementation Unit for Pinrang Regency. This research is an observational research and includes associative research. The number of respondents was 55 employees. To test the hypothesis using path analysis. The results of this study indicate that: 1) The quality of human resources has a positive and significant effect directly or indirectly on the local tax revenue target through excellent service at the Samsat Technical Implementation Unit for the Pinrang Regency, 2) Work discipline has a positive and significant effect directly or indirectly directly to the target of local tax revenue through excellent service at the Samsat Technical Implementation Unit for the Pinrang Regency, and 3) Excellent service has a positive and direct significant effect on the target of local tax revenue at the Samsat Technical Implementation Unit for the Pinrang Regency.